2020
DOI: 10.2139/ssrn.3654390
|View full text |Cite
|
Sign up to set email alerts
|

It’s What You Say and What You Buy: A Holistic Evaluation of the Corporate Credit Facilities

Abstract: We evaluate the impact of the Federal Reserve corporate credit facilities (PMCCF and SMCCF). A third of the positive effect on prices and liquidity occurred on the announcement date. We document immediate pass-through into primary markets, particularly for eligible issuers. Improvements continue as additional information is shared and purchases begin, with the impact of bond purchases larger than the impact of purchases of ETFs. Exploiting cross-sectional evidence, we see the greatest impact on investment grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 20 publications
4
34
0
Order By: Relevance
“… 17 See also O’Hara and Zhou (2020) , Boyarchenko, Kovner, and Shachar (2020) , Kargar et al (2020) , Gilchrist et al (2020) , and D’Amico, Kurakula, and Lee (2020) , who study the effect of Fed interventions during this period on market liquidity and prices along various dimensions. …”
Section: Footnotesmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 See also O’Hara and Zhou (2020) , Boyarchenko, Kovner, and Shachar (2020) , Kargar et al (2020) , Gilchrist et al (2020) , and D’Amico, Kurakula, and Lee (2020) , who study the effect of Fed interventions during this period on market liquidity and prices along various dimensions. …”
Section: Footnotesmentioning
confidence: 99%
“…Several papers focus specifically on liquidity in bond markets in the COVID-19 crisis as well, including O’Hara and Zhou (2020) , Kargar et al (2020) , Fleming and Ruela (2020) , Schrimpf, Shin, and Sushko (2020) , and Boyarchenko, Kovner, and Shachar (2020) . Falato, Goldstein, and Hortaçsu (2020) and Ma, Xiao, and Zeng (2020) focus instead on the sources and implications of large redemption by bond mutual funds.…”
mentioning
confidence: 99%
“…1 Just last year, Mark Carney, the governor of the Bank of England, warned that investment funds that include illiquid assets but allow investors to take out their money whenever they like were "built on a lie" and could pose a big risk to the financial sector. 2 Figure 1 demonstrates the dramatic growth of assets under management of US investment funds investing in corporate bonds in proportion to the size of the corporate-bond market over the last decade since the 2008-2009 crisis. Part of this growth is attributable to the increased regulation of banks, which led market forces to push some of the activities from banks to other market-based intermediaries.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 crisis unfolded quickly in the US and around the world in early 2020, bringing 1 See: https://www.fsb.org/wp-content/uploads/FSB-Policy-Recommendations-on-Asset-Management-Structural-Vulnerabilities.pdf 2 See: https://www.reuters.com/article/us-woodford-inv-suspension-carney/illiquid-investment-funds-built-ona-lie-boes-carney-says-idUSKCN1TR1LK the economy to a halt, and having a major impact on financial markets. Initial declaration of a public health emergency was made in January 31, continuing with various reports of confirmed infections in February.…”
Section: Introductionmentioning
confidence: 99%
“…Our work, therefore, provides insights for understanding the transmission of corporate QE in the US as well. Ongoing research on the Federal Reserve's Corporate Credit Facility has shown that the Fed's policy reduced risk premia, improved liquidity, and led to increased issuance for both investment-grade and high-yield issuers (Boyarchenko et al, 2020;D'Amico et al, 2020;Haddad et al, 2020;O'Hara and Zhou, 2020).…”
Section: Related Literaturementioning
confidence: 99%